Permafrost Dynamics Observatory (PDO): 2. Joint Retrieval of Permafrost Active Layer Thickness and Soil Moisture From L‐Band InSAR and P‐Band PolSAR. Issue 1 (26th January 2023) - Chen, Richard H.; Michaelides, Roger J.; Zhao, Yuhuan; Huang, Lingcao; Wig, Elizabeth; Sullivan, Taylor D.; Parsekian, Andrew D.; Zebker, Howard A.; Moghaddam, Mahta; Schaefer, Kevin M.
Abstract: Seasonal subsidence induced by ground ice melt can be measured by interferometric synthetic aperture radar (InSAR) techniques to infer active layer thickness (ALT) in permafrost regions. The magnitude of subsidence depends on both how deep the soil thawed and how much ice/water content existed in the active layer soil. To provide the later, P‐band polarimetric synthetic aperture radar (PolSAR) backscatter is used due to its sensitivity to subsurface soil moisture and freeze/thaw conditions. In this study, which is the second in a two‐part series of Permafrost Dynamics Observatory (PDO), we exploit L‐band InSAR subsidence and P‐band PolSAR backscatter in a joint retrieval scheme to simultaneously estimate ALT and soil moisture profile of permafrost active layer. Both subsidence and backscatter are explicitly characterized by physics‐based models and share a common set of soil parameters including porosity and water saturation profiles. The PDO joint retrieval has been applied to the L‐ and P‐band SAR data acquired by National Aeronautics and Space Administration/Jet Propulsion Laboratory's Uninhabited Aerial Vehicle Synthetic Aperture Radar over Alaska and western Canada during the 2017 Arctic‐Boreal Vulnerability Experiment (ABoVE) airborne campaign. This high‐resolution (30 m) regional estimates of ALT and soil moisture profile spanning over the ABoVE study domain can help link the ground‐based field surveys with satellite observations to further understand the permafrost and active layer soil process dynamics to disturbances and climate change occurring across the northern circumpolar region. Key Points: We develop a joint retrieval scheme for estimating active layer thickness (ALT) and soil moisture in permafrost soils from L‐band interferometric synthetic aperture radar and P‐band polarimetric synthetic aperture radar observations Modeling of synthetic aperture radar (SAR) observables (surface subsidence and radar backscatter) with respect to active layer soil properties is discussed We present ALT and soil moisture products retrieved from 63 SAR transects acquired during the 2017 NASA Arctic‐Boreal Vulnerability Experiment airborne campaign